Evaluation of industrial Saccharomyces cerevisiae strains for ethanol production from biomass - KASAVİ, CEYDA; TOKSOY ÖNER, EBRU (PERGAMON-ELSEVIER SCIENCE LTD, 2012)
Five industrial Saccharomyces cerevisiae strains were evaluated for their suitability for strain improvement for future use in ethanol production processes. Principal components analysis of growth-related and production-related fermentation parameters of the 5 strains grown on glucose demonstrated the superiority of the Y9 strain in terms of its rapid growth and highest ethanol yields on both biomass and glucose. The growth and ethanol production performances of these strains on various agro-industrial wastes (including sugar beet pulp, starch and sugar beet molasses) and biological residues (including carrot, tomato and potato peel) were also determined. Ethanol tolerance studies, using both solid and liquid cultures, revealed the remarkable abilities of the BC187 and Y9 strains to survive and grow at high ethanol concentrations. Suspension cultures were found to be highly tolerant to 78.80 g L-1 ethanol however their growth ability showed a distinct decrease with increasing ethanol concentration such that only (1-2)% of the control growth was observed in media containing 118.20 g L-1 ethanol. The importance of choosing the appropriate S. cerevisiae strain to be used in ethanol production was clearly established with this study. Fermentation performances of the cultures under different cultivation conditions pointed to the fact that the choice of strain will not only depend on the ethanol tolerance but also on the preferential utilization of the carbon resources of biological residues. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Ethanol; Biomass; Industrial Saccharomyces strains; Ethanol tolerance; Agro-industrial waste; STRESS TOLERANCE; GENES; YEAST; IDENTIFICATION; OPTIMIZATION; PHOSPHORYLATION; FERMENTATION; GRAPE; FUEL